Strategi Pengembangan Pariwisata di Wisata BALKONDES Ngadiharjo di Kawasan Borobudur Kabupaten Magelang - Destiningsih, Rian; Achsa, Andhatu; Verawati, Dian Marlina (JURNAL DESTINASI PARIWISATA; Vol 8 No 2 (2020): VOL 8, NO 2 (2020): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2020)
Magelang has so many tours, nice and very interesting to visit. Balai Ekonomi Desa which is often abbreviated as Balkondes, is a tour that is only found in Magelang. Several tours feature Balkondes, but the destinations carried are different from Balkondes. Balkondes is the embodiment of the village community in developing the economic potential of the village, while the number of Balkondes in Magelang Regency is around 20 Balkondes. One of them, Balkondes Ngadiharjo is one of Balkondes that is unique and still frequently visited by tourists often as tourists. The purpose of this research is provide an overview to identify tourism development strategy in Balkondes Ngadiharjo. The method of the study used descriptive qualitative, Strengths-Weaknesses-Opportunities-Threats (SWOT) and the survey was undertaken on 57 respondents. The results showed that alternative development strategies for Balkondes Ngadiharjo include optimization of promotions, internet access, suitable facilities gave the wide location, environment-based tourism, outdoor events and the tendency to travel in eco-based niche tourism, Borobudur Temple tourists to visit Balkondes Ngadiharjo, increasing creativity Balkondes Ngadiharjo's innovation and uniqueness to maintain competition for the number of visitors between Balkondes and other tours, increase management professionalism, playgrounds, public facilities and innovation and creativity to maintain competition between Balkondes and other tourist objects so that the level of tourist visits is high and can give a positive impression that is memorable for visitors and have an impact on the high profitability of tourist objects.   Keyword : balkondes, tourism, strategy, swot